Diagnosis and management of potentially infectious patients with suspected pulmonary tuberculosis in a developing country setting - González-Angulo, Licé Yulieth (Department of Public Health and Family Medicine, 2015)
This thesis comprises two projects, which focus on simple TB control strategies that can help reduce the risk of M. tuberculosis transmission ... New effective and field-adapted interventions are needed to improve TB programme outcomes. Two projects, which focus on breaking the cycle of TB transmission in developing country settings, are reported.